Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2017
DOI: 10.1016/j.bbalip.2016.10.014
|View full text |Cite
|
Sign up to set email alerts
|

Poor glycemic control in type 2 diabetes enhances functional and compositional alterations of small, dense HDL3c

Abstract: High-density lipoprotein (HDL) possesses multiple biological activities; small, dense HDL3c particles displaying distinct lipidomic composition exert potent antiatherogenic activities which can be compromised in dyslipidemic, hyperglycemic insulin-resistant states. However, it remains indeterminate (i) whether such functional HDL deficiency is related to altered HDL composition, and (ii) whether it originates from atherogenic dyslipidemia, dysglycemia, or both. In the present work we analyzed compositional cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 36 publications
(30 citation statements)
references
References 39 publications
0
21
0
3
Order By: Relevance
“…Multivariate analysis based on PLS regression also unraveled the association of T2DM with the loss of very large HDL, but the association with a gain of small HDL was even stronger (Figure 3). These changes are probably caused by increased CETP activity (9)(10)(11). Opposite to T2DM, CHD is associated with the loss of small and medium-sized HDL and the gain of large HDL (Figure 3).…”
Section: Discussionmentioning
confidence: 99%
“…Multivariate analysis based on PLS regression also unraveled the association of T2DM with the loss of very large HDL, but the association with a gain of small HDL was even stronger (Figure 3). These changes are probably caused by increased CETP activity (9)(10)(11). Opposite to T2DM, CHD is associated with the loss of small and medium-sized HDL and the gain of large HDL (Figure 3).…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, HDL ability to protect LDL oxidation correlates positively with sphingosine-1-phosphate [42] and phosphatidylserine [124] levels. Interestingly, earlier studies have shown an inverse association between phosphatidylcholine-based readily-oxidizable polyunsaturated fatty acid content [125] and antioxidative activity of HDL [126] . Furthermore, such activity is negatively associated with the content of proinflammatory PLs commonly present in these particles, such as phosphatidic acid [127] , [128] , ceramide [124] , [126] and lysophosphatidylcholine [128] .…”
Section: Molecular Components Of Hdl Contributing To Its Antioxidativmentioning
confidence: 96%
“…Interestingly, earlier studies have shown an inverse association between phosphatidylcholine-based readily-oxidizable polyunsaturated fatty acid content [125] and antioxidative activity of HDL [126] . Furthermore, such activity is negatively associated with the content of proinflammatory PLs commonly present in these particles, such as phosphatidic acid [127] , [128] , ceramide [124] , [126] and lysophosphatidylcholine [128] . Finally, both cholesteryl ester and triglyceride content have previously shown negative correlations with antioxidative activity of HDL [124] .…”
Section: Molecular Components Of Hdl Contributing To Its Antioxidativmentioning
confidence: 96%
“… 131 Poor glycemic control in type 2 diabetes enhances functional and compositional alterations of small dense HDL3. 132 Gomez Rosso et al 132 showed that defective functionality of small dense HDL particles was present in patients with type 2 diabetes mellitus with poor glycemic control. The HDL had also diminished its antioxidant ability.…”
Section: Diabetes Dyslipidemia Atherosclerosis and Hdlmentioning
confidence: 99%